ANALISIS PERSEPSI KONSUMEN PADA PRODUK KOSMESTIK BERLABEL HALAL - Lise Purnamasari (Kasaba, 2020)
This study aims to analyze consumer perceptions of cosmetic products labeled halal including the process of selecting, compiling and interpreting information related to these products, so that they finally decide to buy or use them. The research method used is quantitative descriptive analysis. Respondents in this study were 60 students of Djuanda University. The results showed that consumer perceptions of cosmetic products labeled halal were chosen based on their function, besides that Wardah products were also seen as a substitute product for similar products and cosmetic products labeled halal were of interest to a consumer (Muslimah). Therefore, it is important for cosmetic business actors to see these perceptions in order to provide products that are in accordance with consumer perceptions